2016
DOI: 10.1093/europace/euw081
|View full text |Cite
|
Sign up to set email alerts
|

Plasma homocysteine levels predict early recurrence after catheter ablation of persistent atrial fibrillation

Abstract: Plasma Hcy levels are associated with early recurrence of atrial tachyarrhythmia after catheter ablation in persistent atrial fibrillation patients, thus it should be taken into account in prediction of early recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Crosssectional clinical studies indicated that AF patients had elevated homocysteine levels (16,17) and decreased vitamin B6 levels compared with controls (16), whereas a prospective epidemiological study showed no significant association of AF with homocysteine (18). Several observational clinical studies have reported the positive association of homocysteine with recurrent AF risk after ablation (19)(20)(21). Given the close relation of homocysteine with atherosclerotic CVD and AF recurrence, homocysteine may be associated with incident AF in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Crosssectional clinical studies indicated that AF patients had elevated homocysteine levels (16,17) and decreased vitamin B6 levels compared with controls (16), whereas a prospective epidemiological study showed no significant association of AF with homocysteine (18). Several observational clinical studies have reported the positive association of homocysteine with recurrent AF risk after ablation (19)(20)(21). Given the close relation of homocysteine with atherosclerotic CVD and AF recurrence, homocysteine may be associated with incident AF in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the above-described criteria of evaluation, 11 validated articles were included for analysis in our study. [5][6][7][10][11][12][13][14][15][16][17] The main characteristics of the included studies are shown in the Table. Comparisons of homocysteine levels between AF patients and control subjects: Four studies were included in the comparisons of homocysteine levels between AF patients and control subjects. The random-effects model was used since heterogeneity existed (I 2 = 92.7%, P = 0.000).…”
Section: Resultsmentioning
confidence: 99%
“…5 Finally, HHcy has been associated with early recurrence of atrial tachyarrhythmia after procedure of catheter ablation, representing a predictor of early recurrence of atrial fibrillation. 6 As recently highlighted by Spence et al, 7 these observations may be of particular clinical relevance. In fact, in patients undergoing cardiac surgery who developed HHcy, an appropriate homocysteine-lowering treatment with folic acid and methylcobalamin may contribute to prevent atrial fibrillation development, thus improving the outcome of these subjects.…”
mentioning
confidence: 84%